A randomised controlled, trial of the GLP-1 receptor agonist exenatide in idiopathic intracranial hypertension. Issue 6 (27th May 2022) - Mitchell, James; Mollan, Susan; Walker, Jessica; Lyons, Hannah; Yiangou, Andreas; torovic, Zerin Alimajs-; Grech, Olivia; Tsermoulas, George; Brock, Kristian; Sinclair, Alex
Abstract : Background: Pre-clinical data demonstrates the ability of Exenatide, a GLP-1R agonist, to reduce CSF secretion and ICP.1 Existing GLP-1R agonists are widely used to treat obesity and diabetes (but do not cause hypoglycaemia). Methods: Randomised, placebo controlled, double-blind trial of Exenatide in women with active IIH. Participants were randomised 1:1 to Exenatide (10mcg twice daily sub-cutaneous) or placebo for 12 weeks. Telemetric, intraparenchymal ICP monitors (Raumedic) recorded ICP over 12 weeks. Analysis was by hierarchical regression, significance level set at p <0.1 Results: 16 participants were recruited, 15 completed the study: BMI 38.1(6.2) kg/m2, ICP 30.6(5.1) cmCSF. ICP, the primary endpoint, fell significantly (2.5 hours -5.7(2.9) cmCSF (p=0.048), 24 hours -6.4 (2.9) cmCSF (p=0.030) and 12 weeks -5.6 (3.0) cmCSF (p=0.058)). Monthly headache days fell in the Exenatide treated cohort (-7.7 (9.2) p=0.069) and vision improved (logMar acuity -0.1 (0.04) p=0.004). Conclusions: Exenatide reduced ICP acutely and after chronic dosing. GLP-1R agonists represent a new approach to treat IIH. 1. Botfield HF, Uldall MS, Westgate CSJ, Mitchell JL, Hagen SM, Gonzalez AM, Hodson DJ, Jensen RH, Sinclair AJ. A glucagon-like peptide-1 receptor agonist reduces intracranial pressure in a rat model of hydro- cephalus. Sci Transl Med. 2017 Aug 23;9(404):eaan0972. doi: 10.1126/scitranslmed.aan0972. jamesmitchell4@nhs.net 20